BANDERAS, ESCUDOS E IDENTIDADES. UNA APROXIMACIÓN A LA INVENCIÓN DE LA NACIÓN ARGENTINA (1806-1835) - Herrero, Alejandro (Cultura Latinoamericana, 2021)
The image that the Argentine nation has existed since the Colony or since the Revolution and Independence has been questioned for three decades. New interpretations conceive that neither the nation nor Argentina were a given fact, but that both were created in a movement open to different national projects. The aim of this article tries to show that symbols are also part of a construction that historians can reconstruct, and that Buenos Aires, seat of the governments of the Revolution (or central power), created the national symbolism, and tried